2003
DOI: 10.1016/s0005-2736(03)00114-7
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of fluid phase endocytosis coincides with membrane properties of pig platelets

Abstract: In previous studies we have shown that platelets take up low molecular weight molecules from the medium by fluid phase endocytosis, a phenomenon that we previously have used to load trehalose into human platelets, after which we have successfully freeze-dried them. We now extend those findings to a species to be used in animal trials of freeze-dried platelets:pigs. Further, we report results of studies aimed at elucidating the mechanism of the uptake. Temperature dependence of fluid-phase endocytosis was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…Trehalose does not readily cross cell membranes, but can be efficiently loaded into mammalian cells via fluid-phase endocytosis and pinocytosis (3, 40) like other small molecules that do not readily cross membranes (41). Extracellular trehalose is likely acting in the cytosol in the same compartment(s) as the trehalose in the stable cells.…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose does not readily cross cell membranes, but can be efficiently loaded into mammalian cells via fluid-phase endocytosis and pinocytosis (3, 40) like other small molecules that do not readily cross membranes (41). Extracellular trehalose is likely acting in the cytosol in the same compartment(s) as the trehalose in the stable cells.…”
Section: Discussionmentioning
confidence: 99%
“…The limited changes in the fluorophore internalization observed when decreasing the cell temperature, suggest that endocytotic pathways, that are sensibly dependent on the temperature [16,17] in the range 4-37 o C, are only partially effective in the upload process of the c-SLNs and that the internalization is also determined by a direct interaction between the membrane and the c-SLNs phospholipids. This picture agrees with previous analyses [10] that showed that the internalization of the c-SLNs carried fluorophore occurs with the modification of the lipid (SLNs) physical and chemical thermodynamic parameters, probably due to their interaction with phospho-lipids (membrane).…”
Section: Eq 3) In Terms Of the Energy Gain ∆Umentioning
confidence: 99%
“…Several mechanisms of hypothermic injury have been proposed, including the loss of ionic homeothese points corresponds to an activation energy of stasis (31,46), the uncoupling of cellular metabolism decreasing temperature. A swelling mechanism could, however, contribute to cell killing below 10°C because (21), lipid phase transitions in membranes (13,26), depolymerization of the cytoskeleton (49,56), and oxidative k increases with decreasing temperature in this range. However, it is unlikely that cell swelling contributes to stress (8,39).…”
Section: Introductionmentioning
confidence: 99%